Armed groups' modes of local engagement and post-conflict (in)stability: Insights from the Ethiopian and Somali civil wars - Marine Gassier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
What distinguishes post-war governments that succeed in establishing a stable political order and prevent recurring conflict from those that do not? This comparative study considers the specific threats that typically lead to the collapse of the post-conflict political order to offer new hypotheses on the conditions that affect post-war governments' ability to sustainably restore stability. The threats considered include (i) fragmentation of the main actors in the conflict, (ii) inadequate demobilization, and (iii) enduring dependence of the post-war government on local brokers. Post-war regimes are more vulnerable to such risks after wars in which the dominant armed groups have established themselves by co-opting local power structures and drawing on existing socio-political networks, as this process redistributes power from the central to the local level. Empirically, this paper uses a novel dataset documenting the practices through which rebel groups may alter local power structures to highlight the connection between this wartime process of transformation and patterns of conflict recurrence. In addition, it contrasts the transition of the Tigray People's Liberation Front from rebellion to government in Ethiopia in the 1990s with the trajectory of the armed movements in Somalia that also overthrew the incumbent military regime but then failed to establish a viable state.
Keywords: 330; conflict recurrence; post-war regimes; armed groups; Ethiopia; Somalia; comparative study